Comparison of coincidence-anticipation performance of male volleyball players of various levels - Kaynak, K.; Üstünel, A. (International Journal of Applied Exercise Physiology, 2020)
This study, in which 42 male volleyball players, aged between 18 - 28 years participated, seeks to compare the coincidence-anticipation timings of athletes whose sports ages are between 0 - 5, 5 - 10 and 10 - 15 years. For the measurement of the coincidence-anticipation timing of the athletes, the anticipation timer device designed in the laboratory of Erciyes University Faculty of Sport Sciences. The athletes were provided a stimulus at different velocities of 3 mph, 6 mph, 9mph and 12 mph and each athlete was given 5 tries and recorded for 20 times for each velocity, thus administering a total of 100 tests to each athlete. As a result of the measurements and statistical evaluations, while a significant difference P<0.05 was observed between the novice group (0 -5 years) (-24.81±19.99mps) and highly-experienced group (10-15 years) (-4.60±20.34mps) at 6 mph velocity stimulus, no significant difference was found among the other groups. However, regardless of a non-significant difference, it was determined that the highly-experienced group (10-15 years) had better coincidence-anticipation timing when compared to the novice group (0-5 years) and moderately experienced group (5-10 years). It was observed that numeric differences generated better scores with relation to sport experience year.